Dismantled once, diverged forever? A quasi-natural experiment of Red Army misdeeds in post-WWII Europe - Christian Ochsner (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2017)
I study the economic consequences of the Red Army's misdeeds after WWII. I exploit differences in spatial economic activity across the arbitrarily drawn and only for 74 days lasting liberation demarcation line between the Red Army and the Western Allies in South Austria. Dismantling and pillaging, but also (sexual) crimes made regions liberated by the Red Army a less desirable place to live and to start economic activities compared to adjacent regions. Spatial regression discontinuity (RD) estimates show that the liberation causes a relative population decline by around 26 to 31 percent until the present day. Measures of labor productivity also lag behind in Red Army liberated regions. I explain persistence with the selective migration pattern across the demarcation line in the direct aftermath of WWII.
Keywords: J11; N14; N94; R12; R23; 330; Regional economic activity; population shock; dismantling; Red Army; Austria